Don't hesitate communicate effective communication in the office - Pearce, Mark; Dent, Lowisa; Video Education Australasia (Australia : Video Education Australasia, 2010)
This program explores the fundamental business skill of communication in the workplace. The many forms of verbal communication are covered, including oral and written methods such as meetings, speeches, letters and presentations. Similarly, the increasing importance of effective electronic communication is presented
Title from title screen
Executive producer, Simon Garner
Voice over: Jane Lundmark
DVD format
Keywords: Communication in personnel management; Interpersonal communication; Communication in organizations